Retrospective study of feline tracheal mass lesions. Issue 5 (May 2023) - Kanemoto, Hideyuki; Fujiwara-Igarashi, Aki; Kobayashi, Tetsuya; Harada, Kei; Ichimata, Masanao; Kim, Sangho; Hosoya, Kenji; Tomiyasu, Hirotaka; Ohmi, Aki; Tsujimoto, Hajime
Objectives: This multicentre, retrospective observational study aimed to describe the clinical presentation, diagnostic methods, treatment and outcomes of cats with tracheal masses. Methods: Eighteen cats from five academic or secondary/tertiary animal hospitals were included. Results: The median age at diagnosis was 10.7 years (mean 9.5; range 1–17). There were nine castrated males, seven spayed females, one intact male and one intact female. Fourteen (78%) were domestic shorthairs, one (6%) was an Abyssinian, one (6%) was an American Shorthair, one (6%) was a Bengal and one (6%) was a Scottish Fold. The most common presenting complaints included chronic respiratory distress or dyspnoea (n = 14), followed by wheezing/gagging (n = 12), coughing (n = 5) and voice changes (n = 5). There was cervical tracheal involvement in 16/18, and two showed involvement of the intrathoracic trachea. The following methods were used for diagnosis: ultrasound-guided fine-needle biopsy (UG-FNB) and cytology (n = 8), bronchoscopic forceps biopsy and histopathology (n = 5), surgical resection and histopathology (n = 3), forceps biopsy via an endotracheal tube (n = 1) and histology of tissue sputtered from a cough (n = 1). Lymphoma was most often diagnosed (n = 15), followed by adenocarcinoma (n = 2) and squamous cell carcinoma (n = 1). Most lymphoma cases received chemotherapy with or without radiation according to various protocols, and partial (n = 5) or complete responses (n = 8) were noted. Kaplan–Meier survival data for cats with lymphoma revealed a median survival time of 214 days (95% confidence interval >149 days), which was significantly longer than that of other types of tumours (21 days). Conclusions and relevance: Lymphoma was the most prevalent diagnosis, and showed a good response to chemotherapy with or without radiation therapy. Various diagnostic procedures were performed, and UG-FNB and cytology are good diagnostic procedures for cervical tracheal lesions. Owing to the variety of treatment protocols at different centres, it was impossible to compare outcomes.